2019
DOI: 10.3389/fenvs.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Micro- and Nano-Sized Plastic Particles on Benthic Invertebrates: A Literature Review and Gap Analysis

Abstract: As documented by the numerous publications that have appeared in recent years, plastic pollution of the environment and the effects on the respective ecosystems are currently one of the most intensely discussed issues in environmental science and in society at large. Of special concern are the effects of micro-and nano-sized plastics. A key issue in understanding the fate and potential effects of micro-and nano-sized plastics is their dynamic nature, as the size, shape, and charge of the particles change over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(105 citation statements)
references
References 105 publications
0
95
0
10
Order By: Relevance
“…Plastics with higher density than water are expected to sink, but some studies have shown that low-density polymers are also deposited on the substrates of aquatic basins due to biofouling by bacteria, algae, and other organisms [61]. Due to biological processes the density of microplastics in sediments may be several orders of magnitudes higher than that in surroundings water [62]. MPs in Rivers, A Major Route for MP Transport…”
Section: Microplastics In Surface Freshwater Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastics with higher density than water are expected to sink, but some studies have shown that low-density polymers are also deposited on the substrates of aquatic basins due to biofouling by bacteria, algae, and other organisms [61]. Due to biological processes the density of microplastics in sediments may be several orders of magnitudes higher than that in surroundings water [62]. MPs in Rivers, A Major Route for MP Transport…”
Section: Microplastics In Surface Freshwater Systemsmentioning
confidence: 99%
“…As observed above, studies examining the ecotoxicological effect of MPs are still mostly focused on pelagic organisms, while knowledge on toxic effects on benthic organisms is still limited [62]. It can be seen by the articles published since 2010 for all the scientific journals indexed in Scopus that in total 44 studies have been published concerning the impacts of plastic particles on benthic organisms, with the majority on benthic marine organisms and only 10 on freshwater benthos.…”
Section: Ecotoxicological Effects Of Mps On Benthic Organismsmentioning
confidence: 99%
“…The design of more realistic experimental setups with soils is challenging because currently there are only few data on MP contamination in soils and it is not clear whether the MP concentrations found to date in urban (0.3-67.5 g kg −1 ), riparian (0-0.055 g kg −1 ), and agricultural soils (0-42,960 particles kg −1 ) (Helmberger et al, 2019) lead to negative effects on soil biota. Due to detection limits, even less data is available in environmental samples for MP particles <10 ”m (Haegerbaeumer et al, 2019) and thus for the ingestible size range of C. elegans. Given the aliquot of 100 ”l that we gave to each nematode in our experiments, one nematode was effectively exposed to 0.1, 1, and 10 ”g of MP.…”
Section: Discussionmentioning
confidence: 99%
“…Usually plastic fragments measuring up to a size of 100 nm are considered as nanoplastics (NPs); while, plastic fragments ranging between 100 and <5 mm are considered as MPs (Haegerbaeumer, Mueller, Fueser, & Traunspurger, 2019; Koelmans, Besseling, & Shim, 2015a; Moore, 2008). The environmental source of micro/nanoplastics (M/NP) may be primary (from manufactured products) or secondary (transformation of large plastics into small fragments; Maity, Chatterjee, Guchhait, De, & Pramanick, 2019).…”
Section: Introductionmentioning
confidence: 99%